Las especies de Trachelomonas (Algas: Euglenophyta) en tres lagunas volcánicas de Costa Rica - M, Urszula (1995)
The algae of three lakes of volcanic origin, Laguna Hule, Congo and Bosque Alegre (740 m. above see leve!) were studied frorn 1989 to 1993. Five Trachelomonas (Euglenophyta ) species and sorne of their varieties are described. Descriptions and drawings for the following se ven taxa are presented: Trachelomonas volvocinopsis, T. volvocinopsis var. volvocinopsis fo. volvocinopsis, T.intermedia var.intermedia fo. intermedia, T. conica varo conica fo. punctata, T.gracilicostata sp. nov., T. gracilicostata varo reticulata varo nov. and T. raciborskii varo raciborskii. Except for the new taxa, the rest are cosrnopolitan in distribution. The highest amount of inorganic iron, average 13.8 rnglL/depth in 1991-1992 in Laguna Hule, and the highest !lutrient status and seston biornass, could be responsible for the abundance and diversity of Trachelomonas populations in this lagoon.